2010
DOI: 10.1063/1.3310197
|View full text |Cite
|
Sign up to set email alerts
|

Short piston-cylinder pressure cells based on Ni–Cr–Al cylinders and their application to fragile materials

Abstract: In this decade, the performance of piston-cylinder pressure cells has been drastically improved by using robust materials such as nickel-chromium-aluminum and cobalt-nickel-chromium-molybdenum alloys to construct the inner cylinders. In this article, we present several experimental techniques for carrying out resistivity measurements under high pressure by applying the piston-cylinder devices based on the nickel-chromium-aluminum cylinders to fragile materials such as organics. These techniques are, in princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This cell—as its name suggests—has a few-centimeters-thick wall in order to withstand the inner pressure of typically 0.4–0.6 GPa. The wall can be stainless steel or a copper-beryllium alloy, the latter provides a good combination of strength and thermal conductivity [ 36 ]. Typical sample volumes of this type of cell designed for optical experiments are few cm 3 .…”
Section: High Pressure Techniques and Spectroscopic Methods Used In H...mentioning
confidence: 99%
“…This cell—as its name suggests—has a few-centimeters-thick wall in order to withstand the inner pressure of typically 0.4–0.6 GPa. The wall can be stainless steel or a copper-beryllium alloy, the latter provides a good combination of strength and thermal conductivity [ 36 ]. Typical sample volumes of this type of cell designed for optical experiments are few cm 3 .…”
Section: High Pressure Techniques and Spectroscopic Methods Used In H...mentioning
confidence: 99%
“…The highest pressure achieved by this system depends on the sample space dimensions and the materials used in the body-cell cylinders. Close to 5 GPa pressure is reported in such a type of cell using CuBe and NiCrAl alloys with a sample space diameter of 4.4 mm and outer sleeve diameter of 40 mm [2,3]. For inelastic neutron scattering experiments, a pressure up to 1.8 GPa is reached at room temperature in a double-wall cell with 6 mm inner bore and 18 mm outer sleeve diameter [4].…”
Section: Introductionmentioning
confidence: 92%
“…5) and the actual pressure is ∼0.2 GPa, which is comparable to the best pressure-load performance achieved with a PTFE capsule. 29 We have found that the frictional effects can be further reduced by shortening the PTFE puck in the seal assembly but then the seal become less reliable and prone to occasional leaking.…”
Section: Assembly and Testingmentioning
confidence: 94%